Fertility treatments and adverse perinatal outcomes in a population‐based sampling of births in Florida, Maryland, and Utah: a cross‐sectional study. (7th July 2015) - Stanford, JB; Simonsen, SE; Baksh, L
Abstract : Objective: To investigate perinatal outcomes associated with fertility treatments, including assisted reproductive technology (ART), intrauterine insemination with ovulation stimulation (IUI), and ovulation stimulation alone (OS). Design: Population‐representative cross‐sectional survey of women with live births, 2004–2008. Setting: Florida, Maryland, and Utah, USA. Sample: 21 803 women, weighted to represent 1 022 597 women. Methods: Survey and birth certificate data were analysed with logistic regression models adjusted for age, education, race, income, and parity, using separate models for singletons and all births. We used two referent groups: (1) women who never used fertility treatment and (2) subfertile women conceiving without treatment. Main outcome measures: Preterm birth (<37 weeks), very preterm birth (<34 weeks), low birthweight (<2500 g), and very low birthweight (<1500 g). Results: Referent group 1: In singletons, ART was associated with preterm birth (OR 3.28; 95% CI 1.74, 6.20) and low birthweight (OR 2.91; 95% CI 1.99, 4.26). OS was also associated with low birthweight (OR 1.62; 95% CI 1.19, 2.19). Including all births, treatment was associated with preterm birth and low birthweight: ART (OR 6.21; 95% CI 4.21, 9.16 and OR 6.51; 95% CI 4.85, 8.73); IUI (OR 2.10; 95% CI 1.24, 3.56 and OR 2.41; 95% CI 1.54, 3.76); OS (OR 1.40; 95% CI 1.01, 1.94 and OR 2.10; 95% CI 1.60, 2.75), respectively. Referent group 2: ART was associated with both outcomes in all births, but not singletons. Conclusions: Preterm birth and low birthweight associated with fertility treatments are largely attributable to multiple gestation, but are also related to underlying subfertility. Tweetable abstract: Preterm birth is associated with subfertility, and with fertility treatments through multiple gestation. Tweetable abstract: Preterm birth is associated with subfertility, and with fertility treatments through multiple gestation.